The Impact of Perceived COVID-19 Threat and Death Anxiety on Buying Behavior Among Academics: A Comparison Between Türkiye and Northern European Countries - Turna, Gülçin Bilgin; Pekmezci, Halil; IŞIK, OKAY (Türk Kooperatifçilik Kurumu, 2023)
Academics, one of the occupational groups exposed to isolation in the COVID-19 epidemic, tried to adapt to the remote working regulations by not being able to maintain the social environment they were accustomed to in universities. This study aimed to examine the impact of perceived COVID-19 threat and death anxiety on revenge buying behavior by comparing academics who work in Türkiye and Northern Europe (the United Kingdom, the Netherlands, and Norway). “Revenge buying” is a term popularized in the marketing field during the global COVID-19 quarantines. It refers to the surge in shopping desire observed after the lifting of pandemic-related lockdown measures. Data was collected online by using three scales: the “Perceived COVID-19 Threat Scale”, “Templer’s Death Anxiety Scale” and “Revenge Buying Behavior Scale”. The sample consisted of total 327 academics: 163 from Türkiye (TR) and 164 from Northern Europe (NE). Structural Equation Modelling (SEM) was adopted for the analyses. The results showed that academics in NE were more prone to revenge buying behavior than TR. As the perceived threat of COVID-19 and death anxiety increased, it was determined that academics working in both TR and NE have tendencies for revenge buying. However, there was insufficient evidence to support the mediating role of death anxiety in the relationship between perceived COVID-19 threat and revenge buying behavior. In this interdisciplinary study, statistically significant differences identified based on the demographic characteristics of academics working in TR and NE have also been indicated.
Keywords: Perceived COVID-19 Threat; Death Anxiety; Revenge Buying Behavior; Türkiye; Northern Europe